Evaluation of the lingual frenulum in newborns using two protocols and its association with breastfeeding - Maria da C.M. Araujo; Rebeca L. Freitas; Maria Goretti de Souza Lima; Veronica M. da R. Kozmhinsky; Cândida A. Guerra; Geisy M. de S. Lima; Amitis V. Costa e Silva; Paulo Correia de Melo Júnior; Manuela Arnaud; Emídio C. Albuquerque; Aronita Rosenblatt (Brazilian Society of Pediatrics, 2020)
Objective: To characterize the lingual frenulum of full‐term newborns using two different protocols and to assess the association of the lingual frenulum with breastfeeding. Methods: This non‐probabilistic sample consisted of 449 mother/baby binomials. For the anatomo‐functional evaluation of the frenulum, the Neonatal Tongue Screening Test and the Bristol Tongue Assessment Tool were used for the evaluation of the lingual frenulum. Breastfeeding was evaluated using the protocol proposed by UNICEF. Scores were created (good, fair, poor) to evaluate every aspect of the breastfeeding to be observed. The results were analyzed through descriptive and inferential statistics and association tests (Pearson's chi‐squared and Fisher's exact test). Results: The study showed that 14 babies had a lingual frenulum alteration, of whom three had difficulties during suction, requiring frenotomy in the first week of life, whereas 11 had no difficulties during breastfeeding. Regarding the breastfeeding evaluation, 410 mother/baby binomials had good, 36 regular, and three had bad scores. There was a statistically significant association between the tongue‐tie test protocol and breastfeeding (p = 0.028) and between the Bristol Tongue Assessment Tool protocol and breastfeeding (p = 0.028). Conclusion: Alterations in the lingual frenulum are associated with interferences in the quality of breastfeeding and thus, evaluation of the lingual frenulum in newborns is important. Resumo: Objetivo: Caracterizar o frênulo lingual de recém‐nascidos a termo, utilizando dois protocolos diferentes e verificar a relação do frênulo lingual com o aleitamento materno. Método: A amostra não probabilística foi constituída por 449 binômios mãe/bebê. Para a avaliação anatomofuncional do frênulo, utilizou-se o protocolo de avaliação do frênulo lingual para bebês "Teste da Linguinha" e o Bristol Tongue Assessment Tool. A mamada foi avaliada com o protocolo proposto pelo UNICEF. Foram criados escores (bom, regular, ruim) para avaliar cada aspecto da mamada a ser observada. Os resultados foram analisados através de estatísticas descritivas e inferenciais e testes de associação (Qui‐quadrado de Pearson e Exato de Fisher). Resultados: O estudo mostrou que 14 bebês apresentaram alteração de frênulo lingual, nos quais três com dificuldade durante a sucção, necessitando de frenotomia na primeira semana de vida e 11 sem dificuldades durante a amamentação. Quanto à avaliação da mamada, 410 binômios mãe/bebê apresentaram o escore bom, 36 regular e 3 ruim. Houve associação estatisticamente significativa entre o protocolo "Teste da Linguinha" e amamentação (p = 0,028) e entre o protocolo Bristol Tongue Assessment Tool e amamentação (p = 0,028). Conclusão: Alterações no frênulo lingual estão associadas a interferências na qualidade da amamentação, sendo importante a avaliação do frênulo lingual em recém‐nascidos.